2000
DOI: 10.1074/jbc.m908864199
|View full text |Cite
|
Sign up to set email alerts
|

A Small Molecule Antagonist of Chemokine Receptors CCR1 and CCR3

Abstract: We describe a small molecule chemokine receptor antagonist, UCB35625 (the trans-isomer J113863 published by Banyu Pharmaceutical Co., patent WO98/04554), which is a potent, selective inhibitor of CCR1 and CCR3. Nanomolar concentrations of UCB35625 were sufficient to inhibit eosinophil shape change responses to MIP-1␣, MCP-4, and eotaxin, while greater concentrations could inhibit the chemokine-induced internalization of both CCR1 and CCR3. UCB35625 also inhibited the CCR3-mediated entry of the human immunodefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 204 publications
(64 citation statements)
references
References 55 publications
5
59
0
Order By: Relevance
“…Additionally, eosinophils from some donors exhibit a significant expression of CCR1 and respond effectively to its ligand MIP-1␣/ CCL3 (14). Similar results have now been seen by other groups (17), and we have shown that responses of eosinophils to chemokines can be blocked by chemokine receptor antagonists with theoretical benefits for the treatment of allergic inflammation (18). However, activated complement fragments such as C5a and C3a, formylated peptides (formyl-methionyl-leucylphenylalanine), and a wide variety of lipid mediators can also induce similar responses in eosinophils (19 -22).…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Additionally, eosinophils from some donors exhibit a significant expression of CCR1 and respond effectively to its ligand MIP-1␣/ CCL3 (14). Similar results have now been seen by other groups (17), and we have shown that responses of eosinophils to chemokines can be blocked by chemokine receptor antagonists with theoretical benefits for the treatment of allergic inflammation (18). However, activated complement fragments such as C5a and C3a, formylated peptides (formyl-methionyl-leucylphenylalanine), and a wide variety of lipid mediators can also induce similar responses in eosinophils (19 -22).…”
supporting
confidence: 68%
“…Leukocyte Shape Change Assays-Eosinophil, monocyte, basophil, and neutrophil shape change was assayed as described in previous work (14,18,30). Stimulation of these leukocytes by chemoattractant and chemokinetic agonists results in changes in cell shape that are measured as changes in their ability to scatter light when illuminated in a flow cytometer (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, no internalization was induced by natural chemokines acting as antagonists including I-TAC, IP10, and Mig, which bind to CCR3 (35), eotaxin, which binds to CCR2 (44), and MCP-3, which binds to CCR5 (45). Like the chemokine-based antagonists, small-molecule antagonists were unable to down-regulate chemokine receptors, as shown for TAK-779, which binds to CCR5 (66) and for UCB35625, which binds to CCR1 and CCR3 (67). These data indicate that, as a rule, the blockade of chemokine receptors by antagonists mainly depends on receptor occupancy.…”
Section: Inhibition Of Chemotaxis and [Ca 2ϩ ] I Changes By I-tac (4 -mentioning
confidence: 93%
“…The cells were washed in RPMI ϩ 0.5% BSA ϩ 25 mM HEPES (pH 7.4) (binding buffer), counted, and resuspended in binding buffer at a density of 2 ϫ 10 7 cells/ml. The assay was carried out as previously described (34). Briefly, cells were incubated with 0.1 nM 125 I-huMDC and increasing concentrations of unlabeled huMDC or muMDC for 60 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%